SUPPORT FOR GIFTED STUDYING YOUTH: LEGAL AND SOCIO-PEDAGOGICAL ASPECTS - Hryshchuk, Yuliia V. (Educological discourse, 2014)
In the article analyzes the main areas of support gifted students. Characterized the social, psychological and educational problems of gifted students; defined social and educational conditions, compliance with which ensures the efficiency of support. The author stresses the need to establish support programs and special programs for training and retraining of educational personnel working with gifted students.